Potential cost-effectiveness for using patient decision aids to guide osteoporosis treatment. Issue 9 (September 2016) - Penton, H.; Hiligsmann, M.; Harrison, M.; Reginster, J.-Y.; Boonen, A.; Bansback, N.
Abstract Summary We use a model to predict whether using a patient decision aid in patients considering bisphosphonate therapy would be a good use of health resources. We found that if the decision aid improved adherence, and only marginally increased time physicians needed with their patients, then the decision-aid would be cost-effective. Introduction Oral bisphosphonates have been shown to reduce the risk of osteoporotic fracture. Adherence is crucial but suboptimal. A recent study suggests that a patient decision aid, which facilitates shared decision-making, could be effective in increasing adherence to bisphosphonates. But decision aids come at a cost in terms of additional time spent with physicians. This study considers the emerging evidence on the role of patient decision aids in improving adherence to bisphosphonates and their potential costs to inform future decision-making and research priorities. Methods We estimate the hypothetical cost-effectiveness of a patient decision aid detailing the benefits and risks of bisphosphonates for osteoporotic patients, from a Canadian healthcare perspective. A previously developed and validated Markov microsimulation model was adapted to include use of a patient decision aid to support the decision of whether to initiate bisphosphonate therapy, and subsequent influence on adherence and future fractures. We considered 2014 costs and benefits in terms of quality-adjusted life-years (QALYs). Results A patient decision aid that could improve treatment initiation rates or persistence (adherence) by 20 %, or a linear combination of the two, in osteoporotic women aged 70+ over a 3-year treatment period was found to have an incremental cost-effectiveness ratio below 50, 000/QALY. Conclusions Patient decision aids have the potential to be cost-effective in osteoporosis so long as they increase adherence under certain conditions. Funding further research on the long-term effectiveness and costs of a patient decision aid which outlines all treatment options for osteoporosis patients is justified.